Seismic Analysis of the Detachment and Impact Phases of a Rockfall and Application for Estimating Rockfall Volume and Free‐Fall Height. Issue 11 (20th November 2019) - Le Roy, G.; Helmstetter, A.; Amitrano, D.; Guyoton, F.; Le Roux‐Mallouf, R.
Abstract: We analyzed 21 rockfalls that occurred in limestone cliffs of the Chartreuse Massif (French Alps). These rockfalls were detected both by Terrestrial Laser Scanning or photogrammetry and by a local seismological network. The combination of these methods allowed us to study relations between rockfall properties (location of detachment and impacts areas, volume, geometry, and propagation) and the induced seismic signal. We observed events with different propagation modes (sliding, mass flow, and free fall) that could be determined from digital elevation models. We focused on events that experienced a free fall after their detachment. We analyzed the first parts of the seismic signals corresponding to the detachment phase and to the first impact. The detachment phase has a smaller amplitude than the impact phase, and its amplitude and duration increases with rockfall volume. By measuring the time delay between the detachment phase and the first impact, we can estimate the free‐fall height. We found a relation E s = aE p b between the potential energy of a rockfall E p and the seismic energy E s generated during an impact, with a = 10 −8 and b = 1.55 and with a correlation coefficient R 2 = 0.98. We can thus estimate both the potential energy of a block and its free‐fall height from the seismic signals. By combining these results, we obtain an accurate estimate of the rockfall volume. The relation between the E p and E s was tested on different geological settings and for larger range of volumes using Yosemite, Mount Granier rockfalls, and with a data set of controlled releases of blocks (Hibert et al., 2017, https://doi.org/10.5194/esurf‐5‐283‐2017, https://www.earth‐surf‐dynam.net/5/283/2017/ ). Key Points: Rockfall detachment, free fall, and impact can be distinguished on a rockfall seismogram Seismic energy of the first impact phase is well correlated with the potential energy of the rockfall and allows an estimation of its volume Seismic energy and duration of the detachment signal increase with rockfall volume